Determining Awareness among Medicine and Nursing Units: Ethical and Social Aspects of Organ Donation from a Living Donor Based on Altruistic Motives in Israel and How the Various Religious and Their Members Change Regarding Saving Lives in the Context of Organ Donation - Tarabeih, Mahdi; Awawdi, Khaled; Rakia, Riad Abu (Issues and Development in Health Research Vol. 6, 2021)
Objectives: The authors of this study were doubtful as to whether the risks of live kidney donation had been adequately studied and protected against. The purpose of this study was to look into the rigour and safety of current live donation process in Israel. Background: From 2015-2017, 65% of all kidney donations in Israel were live donations. Methods: The researchers polled 91 Israelis who had given a kidney. The questionnaire inquired about the pre-donation process, including whether and how risks were communicated to donors, post-donation illness/complications, and medical follow-up.Also, whether the donors felt supported, confident and well-advised. Results: Creatinine levels increased significantly after donation, with the youngest donors (18-29) having the highest levels.None of the donors were followed up on by a nephrologist, but only by their GP, and none had more than two follow-up visits. Despite the elevated creatinine levels, none were referred to a nephrologist for treatment or monitoring.The risk information provided to the donors also reveals gaps and inadequacies. Conclusions: The authors give suggestions to improve the live donation procedure by making it more rigorous, cautious, well-followed, and research-based. It's also critical to take active steps to increase the number of deceased donations. Each deceased donation equates to one less live donation, resulting in less harm to healthy individuals.